Implementation of Good Maufacturing Practices (GMP) in the Kitchen Hospital - Fitria Novita Sari (Universitas Airlangga, 2016)
Abstract: Food safety is one of the important thing in public health improvement in Indonesia. Hospitals are required to keep food safety for patients by conducting the principle Good Manufacturing Practices (GMP). The purpose of this research to -identify the application of GMP in Installation Nutrition Hospital. Design of this study was using descriptive research in observational method with cross sectional design. Variables the treatment were the physical building, utility, equipment, storage, and food handlers. Data collection was done by observation and interview. The research results show that the variable subjects enough to fulfi l with Kepmenkes No. 1204 of 2004 and Thaheer, 2008. But there were several that must be considered as location, building, fl oor, ventilation, lighting, kitchens temperature, storage temperature of food that were not appropriate. sorting and processing of solid waste, hand washing facilities, drink water quality, storage temperature of food that were not appropriate, behavior the use of a mask and gloves while working. This suggestion are increase the open window as ventilation, turning lights when a food processing, adding exhauster for good air circulation, do the processing of solid waste, given the tool dryer, controlling at a temperature storage food, health check on rectal swab of food handlers is routinely, and sanctions or fi ne associated disobedience of food handlers in the use of mask and gloves while working.Keywords: Good Manufacturing Practices, food handlers, food safety